PEMBERDAYAAN MASYARAKAT DALAM KEGIATAN GERAKAN PELESTARIAN LINGKUNGAN DI KELURAHAN TELAGA SARI KOTA BALIKPAPAN - Saraswati, Wiwik; Anam, Hairul; Hadiyatno, Didik; Yuliani, Tutik (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2024)
Communities in the telagasari environment need to carry out environmental greening activities to maintain environmental quality and protection. This activity method is carried out using persuasive approaches, emipric, normatic and educational approaches, and androgogy approaches with the aim of increasing community participation and KKN students in environmental greening activities. Greening activities are carried out through planting trees and providing knowledge and understanding to the community about the importance of preserving the environment. By increasing water absorption and supporting activities that can improve environmental quality, it can prevent flooding and make the environment beautiful and shady.